2015
DOI: 10.1007/s00276-015-1583-8
|View full text |Cite
|
Sign up to set email alerts
|

Technical difficulties of left colic artery preservation during left colectomy for colon cancer

Abstract: Left colic artery preservation is highly feasible at its origin in more than two-thirds of cases due to the separate origin. The addition of a high IMV ligation increases the risk of damage to the LCA at the inferior border of the pancreas because the distance to the IMV is less than 20 mm in two-thirds of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
2
24
0
4
Order By: Relevance
“…This did not significantly increase total operating time. Some studies30 31 have reported that an IMA branching pattern with a large distance between the origins of the IMA and LCA causes technical difficulty. It would appear that surgeons should not hesitate to change the tie level of the IMA when performing a difficult low‐tie ligation.…”
Section: Discussionmentioning
confidence: 99%
“…This did not significantly increase total operating time. Some studies30 31 have reported that an IMA branching pattern with a large distance between the origins of the IMA and LCA causes technical difficulty. It would appear that surgeons should not hesitate to change the tie level of the IMA when performing a difficult low‐tie ligation.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, during dissection of the LCA, extreme caution should be taken, and ligation of the SMV was performed first in order to avoid any damage to the IMV. Although there is still uncertainty with regard to the technical difficulty of the procedure, Sekimoto et al[ 17 ] have demonstrated that compared to the high-tie technique, the low-tie procedure did not prolong the operating time and did not increase the amount of intraoperative bleeding. In the present study, compared with other previous studies on high ligation, the operating time was not prolonged significantly[ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is still uncertainty with regard to the technical difficulty of the procedure, Sekimoto et al[ 17 ] have demonstrated that compared to the high-tie technique, the low-tie procedure did not prolong the operating time and did not increase the amount of intraoperative bleeding. In the present study, compared with other previous studies on high ligation, the operating time was not prolonged significantly[ 17 , 18 ]. In addition, the incidence of postoperative complications was relatively low owing to the familiarity with anatomy and meticulous operation.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic rectal cancer surgery has been proven to have the same clinical results as traditional open surgery in terms of safety and e cacy [4,5]. During the laparoscopic low anterior resection of rectal cancer, the inferior mesenteric artery (IMA) can be treated in two ways: one is to identify and preserve the left colic artery (LCA) while ligating the IMA after the bifurcation of the left colic artery, the other is to ligate directly the root of the IMA without preserving the LCA [6].…”
Section: Introductionmentioning
confidence: 99%